The determinants of cash holdings and characteristics of the industrial business cycle in Indonesia - Sari, Linda Purnama; Kurniawati, Sri Lestari; Wulandari, Dewi Ayu (University of Merdeka Malang, 2019)
One of the motives of a business doing cash holdings is the precautionary motive. The company tries to accumulate cash as a precautionary measure to cover unanticipated future necessities. We investigate to determine the factors that can affect company cash holdings that are associated with the characteristics of the industrial business cycle in Indonesia. The sample used is companies that meet the criteria (purposive sampling) and are grouped into different industrial characteristics, such as sensitive industry, defensive industry, growth industry, and cyclical industry. This enables to understand the behavior of cash holdings in a different industry. The analysis technique used is the data panel regression analysis. We find that each type of industry has different characteristics in maintaining its cash balance. For defensive industry and growth industry hold more cash than other industry, because they have strong growth opportunities. In addition, we find that inflation, managerial ownership, leverage, dividend policy, investment opportunities, and firm size have an effect on cash holdings while the operating cycle has no effect on cash holdings.JEL Classification: G32, G35, G38DOI: https://doi.org/10.26905/jkdp.v23i4.3326